Memory CD4+ T-Cell Lymphocytic Angiopathy in Fatal Forms of COVID-19 Pulmonary Infection - Guihot, Amélie; Plu, Isabelle; Soulié, Cathia; Rousseau, Alice; Nakid-Cordero, Cecilia; Dorgham, Karim; Parizot, Christophe; Litvinova, Elena; Mayaux, Julien; Malet, Isabelle; Quentric, Paul; Combadière, Béhazine; et al. (Frontiers in Immunology, 2022)
Immunopathological pulmonary mechanisms leading to COVID-19-related death in adults remain poorly understood. Broncho-alveolar lavage (BAL) and peripheral blood sampling were performed in 72 steroid and non-steroid-treated intensive care unit (ICU) patients (23-75 years; 44 survivors). Peripheral effector SARS-CoV-2-specific T cells were detected in 34/58 cases, mainly directed against the S1 portion of the spike protein. The BAL lymphocytosis consisted of T- cells while the mean CD4/CD8 ratio was 1.80 in non-steroid treated patients and 1.14 in steroid-treated patients. Moreover, strong BAL SARS-CoV-2 specific T cell responses were detected in 4/4 surviving and 3/3 non-surviving patients. Serum IFN-g and IL-6 levels were decreased in steroid-treated patients when compared to non-steroid treated patients. In lung samples from 3 (1 non-ICU and 2 ICU) additional deceased cases, a lymphocytic memory CD4 T cell angiopathy was observed, co-localizing with SARS-CoV-2 was observed. Taken together, these data show that disease severity occurs despite strong anti-viral CD4T cell specific responses migrating to the lung, whichcould suggest a pathogenic role for perivascular memory CD4 T cells upon fatal COVID-19 pneumonia.